"It's a Book I Might Well Wish to Have Signed My Name To": The Collected Kulchur Book Reviews of Ted Berrigan. Issue 1 (2nd January 2018) - Birmingham, Jed
ABSTRACT: Kulchur, a little magazine of cultural commentary, enjoyed a run of 20 issues between 1960 and 1966. The magazine established its reputation based on its unique critical voice, in part supplied by reviews penned by poet Ted Berrigan. Berrigan's highly personal, "careless" book reviews helped to inform and establish the magazine's critical stance. This article provides an historical overview of Kulchur and assesses Berrigan's contributions to the magazine.